Effectiveness of Pilates Training on Body Composition and Isokinetic Muscular Strength in Adolescent Baseball Players - Yook, Jang Soo; Kim, Da Yoon; Choi, Dong Hun; Ha, Min-Seong; Hwang, Yoon Young (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Body composition and muscular strength are important for baseball skills and successful performance. Conditioning training programs have the potential to enhance athletic performance via physiological changes. In this single-group interventional study, we investigated the effect of 8 weeks of Pilates training (PT) on contralateral and regional body composition, and isokinetic muscular strength in knee and trunk flexion/extension in adolescent baseball players. In our results, PT increased both right- and left-sided lean mass in the trunk. Following PT, work per repetition and average power showed significant increases in the flexion and extension of the left knee only. PT significantly decreased the peak torque of the trunk flexor and increased the average power of the trunk extensor. In addition, the ratio of the trunk flexion/extension strength of peak torque showed a decreasing trend, whereas that of work and average power did not change significantly following PT. In conclusion, PT evenly improved lean mass on both the right and left sides of the body. Knee and trunk strength increased after PT. Our findings suggest that PT may be a useful strategy for enhancing athletic performance in regard to the muscular strength of adolescent baseball players.